CONTEMPORARY ISLAMIC DYNAMICS IN FRANCE AS A REPRESENTATION OF SECULAR STATES IN EUROPE: BETWEEN CHALLENGES AND OPPORTUNITIES - Salma Ali Salem Mansoor Alawlaqi; Ahmad Kholil; Laily Fitriani; Zekeriya kasap (Universitas Muhammadiyah Makassar, 2026)
This study explored the dynamics of contemporary Islam in France as a representation of secular European countries through critical discourse analysis to examine the interaction between Islamic religious identity and the principles of secularism (laïcité). It is based on socio-cultural and political literature that highlights the increasing tension between the religious values of Muslims and the demands of citizenship in modern secular societies. Although numerous studies on secularism have been conducted, few have highlighted how Muslims in France experience and negotiate their religious identity under the pressure of state neutrality. This study aimed to analyze Muslim religious practices in the French secular context, identify the main challenges they face, and explore adaptation strategies to maintain religious identity while adjusting to secular values. Data was collected from international news reports discussing the banning of long clothing in schools, employment discrimination, and increasing anti-Muslim actions. The results demonstrated that public discourse in France frames Islam as a ‘potential threat’ to secularism, thereby legitimizing the state's restrictive policies and symbolic exclusion. However, Muslim communities continue to evidence resistance through selective adaptation and the preservation of religious practices in the private sphere. These findings enrich our understanding of the relationship between religion and politics in Europe and offer critical insights into cultural pluralism amid rising nationalism and rigid secularism.